A Novel Iron Transporter SPD_1590 in Streptococcus pneumoniae Contributing to Bacterial Virulence Properties - Miao, Xinyu; He, Jiaojiao; Zhang, Liang; Zhao, Xinlu; Ge, Ruiguang; He, Qing-Yu; Sun, Xuesong (Frontiers in Microbiology, 2018)
Streptococcus pneumoniae, a gram-positive human pathogen, has evolved three main transporters for iron acquisition from the host: PiaABC, PiuABC, and PitABC. Our previous study had shown that the mRNA and protein levels of SPD_1590 are significantly upregulated in the piuA/piaA/pitA triple mutant, suggesting that SPD_1590 might be a novel iron transporter in S. pneumoniae. In the present study, using spd1590-knockout, -complemented, and -overexpressing strains and the purified SPD_1590 protein, we show that SPD_1590 can bind hemin, probably supplementing the function of PiuABC, to provide the iron necessary for the bacterium. Furthermore, the results of iTRAQ quantitative proteomics and cell-infection studies demonstrate that, similarly to other metal-ion uptake proteins, SPD_1590 is important for bacterial virulence. Overall, these results provide a better understanding of the biology of this clinically important bacterium.